2021
DOI: 10.3390/molecules26123540
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Sequential One-Pot Synthesis of 8-Substituted Pyrazolo[1,5-a][1,3,5]triazines

Abstract: This paper reports a convenient sequential one-pot approach for the synthesis of an array of 14 pyrazolo[1,5-a][1,3,5]triazines, substituted in C8 by halogen (Br), various functions (CN and CO2Et) and alkyl or (het)aryl groups. This study confirms the interest of combining the efficient heating obtained under dielectric microwave heating and the achievement of sequential one-pot reactions, avoiding the tedious work-up and purification of intermediate compounds, achieving sustainable synthesis processes. Consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Our previous studies on the use of microwaves for the synthesis of heterocyclic systems frequently demonstrated that controlling and optimizing the conditions of such organic reactions performed in sealed tubes may be trickier than with systems operating at atmospheric pressure. [26][27][28] It often requires a large number of trials in which irradiation has to be stopped and glassware cooled before opening vials and taking aliquots. To overcome these drawbacks, we envisioned the use Raman spectrometry to live-monitor the reaction outcome in the sealed tube.…”
Section: Psp Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies on the use of microwaves for the synthesis of heterocyclic systems frequently demonstrated that controlling and optimizing the conditions of such organic reactions performed in sealed tubes may be trickier than with systems operating at atmospheric pressure. [26][27][28] It often requires a large number of trials in which irradiation has to be stopped and glassware cooled before opening vials and taking aliquots. To overcome these drawbacks, we envisioned the use Raman spectrometry to live-monitor the reaction outcome in the sealed tube.…”
Section: Psp Synthesismentioning
confidence: 99%
“…This paper describes the achievement of an innovative microwave-assisted procedure of the targeted products via a catalyst-free multicomponent reaction (MCR) in ethanol as a bio-based and reusable solvent. Our previous studies on the use of microwaves for the synthesis of heterocyclic systems frequently demonstrated that controlling and optimizing the conditions of such organic reactions performed in sealed tubes may be trickier than with systems operating at atmospheric pressure [26][27][28]. It often requires a large number of trials in which irradiation has to be stopped and glassware cooled before opening vials and taking aliquots.…”
Section: Introductionmentioning
confidence: 99%